LITERATURE REVIEW: ANALISIS BIAYA MANFAAT PENGARUH PENGGUNAAN ALAT BANTU MANUAL PATIENT HANDLING TERHADAP RISIKO MUSCULOSKELETAL DISORDERS - Maarifah Dahlan (J-KESMAS: Jurnal Kesehatan Masyarakat, 2026)
Musculoskeletal Disorders (MSDs) are common occupational health problems experienced by healthcare workers, particularly nurses, due to manual patient handling activities involving high biomechanical loads. These conditions may lead to musculoskeletal pain, decreased productivity, work absenteeism, and increased healthcare costs. This literature review aimed to analyze the effectiveness of manual patient handling assistive devices in reducing the risk of MSDs and to examine the concept of cost-benefit analysis in workplace ergonomic implementation. Literature searches were conducted through PubMed and Google Scholar using the keywords “Manual Patient Handling,” “MSDs,” and “Cost Benefit Analysis.” The selected articles were relevant scientific publications from the last ten years. The findings showed that the use of assistive devices such as exoskeletons, robotic transfer systems, air-assisted devices, wearable lift-assist vests, and patient-handling technology could reduce biomechanical loads, excessive muscle activity, and the risk of MSDs among healthcare workers. In addition to improving occupational safety and comfort, these devices also have the potential to enhance service efficiency. However, their implementation still faces challenges, including high procurement costs, training requirements, and limited healthcare facilities. Cost-benefit analysis is an important approach for assessing the feasibility of ergonomic implementation in supporting occupational safety and healthcare worker productivity.Keywords: Manual Patient Handling, Musculoskeletal Disorders, ergonomics, healthcare workers, cost-benefit analysis.